The world is random: a cognitive perspective on perceived disorder - Kotabe, Hiroki P. (Frontiers in Psychology, 2014)
Research on the consequences of perceiving disorder is largely sociological and concerns broken windows theory, which states that signs of social disorder cause further social disorder. The predominant psychological explanations for this phenomena are primarily social. In contrast, I propose a parsimonious cognitive model (“world-is-random” model; WIR), which basically proposes that disorder primes randomness-related concepts, which results in a reduction in and threat to the sense of personal control, which has diverse affective, judgmental, and behavioral consequences. I review recent developments on the psychological consequences of perceiving disorder and argue that WIR can explain all of these findings. I also cover select correlational studies from the sociological literature and explain how WIR can at least partly explain for their diverse findings. In a general discussion, I consider possible alternative psychological models and argue that they do not adequately explain the most recent psychological research on disorder. I then propose future directions which include determining whether perceiving disorder causes a “unique psychology” and delimiting boundary conditions.